1964
DOI: 10.1126/science.146.3647.1038
|View full text |Cite
|
Sign up to set email alerts
|

Electroconductive Polymers

Abstract: Polymers of a new type with an unusual combination of properties have been synthesized. They are of high molecular weight, they are soluble in organic solvents, and they can be cast as films. Their electrical conduction is electronic in the solid state and can be controlled up to a conductivity of 10(-2) ohm(-1) cm(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…For example, the T g and M n values of OH-terminated polymers with DB ¼ 8% (M n ¼ 14,500 Da, T g ¼ 155 C) and DB ¼ 50% (M n ¼ 17,000 g/mol, T g ¼ 152 C), were close to each other. This finding was also in accordance with that observed previously by Wooley et al [114], where linear, hb, and dendritic polyesters containing an identical amount of phenolic -OH groups per unit showed similar T g values in the range 197-204 C. 36 A. Ghosh et al Voit and coworkers [115] prepared hb polyesters by solution polycondensation at room temperature from the previously reported monomer, namely 3,5-bis (trimethylsiloxy)-benzoyl chloride (Scheme 2, 1-2) [109,110]. Fully soluble aromatic AB 2 hb polyesters with a DB of about 55% in very high yield (~98 %) and of high molar mass (M w ¼ 45,000 Da) were achieved, which was in accordance with results previously reported in the literature [79,108].…”
Section: Hyperbranched Poly(aryl Ester)ssupporting
confidence: 86%
See 3 more Smart Citations
“…For example, the T g and M n values of OH-terminated polymers with DB ¼ 8% (M n ¼ 14,500 Da, T g ¼ 155 C) and DB ¼ 50% (M n ¼ 17,000 g/mol, T g ¼ 152 C), were close to each other. This finding was also in accordance with that observed previously by Wooley et al [114], where linear, hb, and dendritic polyesters containing an identical amount of phenolic -OH groups per unit showed similar T g values in the range 197-204 C. 36 A. Ghosh et al Voit and coworkers [115] prepared hb polyesters by solution polycondensation at room temperature from the previously reported monomer, namely 3,5-bis (trimethylsiloxy)-benzoyl chloride (Scheme 2, 1-2) [109,110]. Fully soluble aromatic AB 2 hb polyesters with a DB of about 55% in very high yield (~98 %) and of high molar mass (M w ¼ 45,000 Da) were achieved, which was in accordance with results previously reported in the literature [79,108].…”
Section: Hyperbranched Poly(aryl Ester)ssupporting
confidence: 86%
“…As an example, Yuan et al [108] were able to activate hard carbon spheres with initially low surface areas in molten KOH at 600 C for 1-2.5 h. Measurements showed that depending on the KOH/carbon ratio, the specific surface areas could increase to more than 1,100 m 2 /g. Elsewhere, solid carbon spheres derived from glucose have been activated with KOH, resulting in a 100-fold increase of their surface area from 13.9 to 1,283 m 2 /g [109]. Meanwhile, although some other researchers have failed to increase the BET surface area from low surface area carbon spheres, they were nevertheless able to achieve satisfactory adsorption of compounds during experimentation [110].…”
Section: Chemical Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Di(2,4,4-triganic solvents are limited to materials doped with methylpentyl)dithiophosphinic acid (82%) was obelectron transfer agents. 2 These gels transition tained from Cytec Industries, Inc. and was purified when ionized due to the charge transfer reactions.…”
Section: Introductionmentioning
confidence: 99%